2000
DOI: 10.1136/heart.83.3.267
|View full text |Cite
|
Sign up to set email alerts
|

Racial variation in cardiovascular morbidity and mortality in essential hypertension

Abstract: Objectives-To perform a longitudinal comparison of morbidity and mortality among white, south Asian and Afro-Caribbean hypertensive patients in relation to baseline demographic characteristics and clinic and ambulatory blood pressure variables. Design-Observational follow up study. Setting-District general hospital and community setting in Harrow, England. Patients-528 white, 106 south Asian, and 54 Afro-Caribbean subjects with essential hypertension who had undergone 24 hour ambulatory intra-arterial blood pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 21 publications
3
63
1
Order By: Relevance
“…In three studies of clinically selected adults [17][18][19] (hence excluded from the tables), two reported higher hypertension prevalence rates 17,18 and one reported similar BP levels 19 in people from African descent compared to white adults. Table 2 First author surname and date of publication (continued)…”
Section: Key Findingsmentioning
confidence: 99%
“…In three studies of clinically selected adults [17][18][19] (hence excluded from the tables), two reported higher hypertension prevalence rates 17,18 and one reported similar BP levels 19 in people from African descent compared to white adults. Table 2 First author surname and date of publication (continued)…”
Section: Key Findingsmentioning
confidence: 99%
“…While the lower blood pressure in Bangladeshis was associated with lower BMI, differences in obesity clearly did not account for much of the ethnic variation. Three studies [15][16][17] on adults, which were excluded from this review because they were based on clinically selected patients study, reported lower blood pressure levels in the South Asian population than in the white population.…”
Section: Blood Pressure Of South Asian Adults In the Ukmentioning
confidence: 99%
“…In the UK, multiple researchers have noted higher prevalence rates of hypertension in populations of African ancestry but lower rates of CVD mortality when compared to their hypertensive white and South Asian cohorts. 71,72 These mismatches between hypertension and CVD risk in ethnic subgroups suggest that the MetS hypertension criteria should be altered by either changing the cutoffs for different populations or weighting the individual criteria based on their risk contribution to CVD in each population. In the extreme case, one could also argue for the omission of hypertension from the MetS criteria in ethnic groups where the relationship between hypertension and CVD risk is poor.…”
Section: Found That There Was No Significant Association Betweenmentioning
confidence: 99%